Christian Religious Education Teacher Understanding on Work Professionality and Its Implementation as Educators - Rosnila Hura (Budapest International Research and Critics University, 2022)
The title “teacher” is a noble designation because the teacher is not just a teaching profession but a very noble task. It is not easy being a teacher, because the teacher does not only teach but also has to be able to accompany children and even be an example for their students. Praise the teachers who always fight for the students who are educated. However, the awareness of the professional duties of a teacher has not been shared by all teachers, there are still those who only see that being a teacher is a tool/field to earn a living. Indeed, this is not wrong, because every person who holds a profession has the right to get a wage or salary. But the problem is that if due to a small salary, the teacher does not carry out his duties properly, in the end it is the students or students who are disadvantaged. The list of teachers in the school is quite large, but it often happens that the class becomes empty because the teacher is not in the class to teach. It is easy for teachers to change schools because they want to find a school that promises more honorariums, even though the school where they teach really needs teachers. Of course, seeing this, the question arises